1992
DOI: 10.1113/jphysiol.1992.sp019124
|View full text |Cite
|
Sign up to set email alerts
|

Role of proton pump of mitochondria‐rich cells for active transport of chloride ions in toad skin epithelium.

Abstract: SUMMARY1. Active Cl-currents were studied in short-circuited toad skin epithelium in which the passive voltage-activated Cl-current is zero. Under visual control doublebarrelled microelectrodes were used for impaling principal cells from the serosal side, or for measuring the pH profile in the solution bathing the apical border.2. The net inward (active) 36CP-flux of 27+8 pmol s-1 cm-2 (16) (mean + s.E.M (number of observations)) was abolished by 2 mM-CN-(6-3 ± 3-5 pmol s-1 cm-2 (8)). The active flux was maint… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
29
0

Year Published

1992
1992
2016
2016

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(32 citation statements)
references
References 23 publications
3
29
0
Order By: Relevance
“…Since the measured membrane potential of -100 mV was close to the potassium equilibrium potential, which in our preparation was -106 + 2 mV, n = 55 (Larsen, Willumsen & Christoffersen, 1992), our results indirectly indicate that a K+ conductance becomes activated by the increased intracellular [cyclic AMP]. To account for the increase in fRb such K+ conductance must be in the apical membrane.…”
Section: Principal Cellsmentioning
confidence: 83%
“…Since the measured membrane potential of -100 mV was close to the potassium equilibrium potential, which in our preparation was -106 + 2 mV, n = 55 (Larsen, Willumsen & Christoffersen, 1992), our results indirectly indicate that a K+ conductance becomes activated by the increased intracellular [cyclic AMP]. To account for the increase in fRb such K+ conductance must be in the apical membrane.…”
Section: Principal Cellsmentioning
confidence: 83%
“…For example, an efflux of protons is generated by an apical proton pump in MR cells (Page & Frazier, 1987;Ehrenfeld, Lacoste & Harvey, 1989;Harvey, 1992;Larsen, Willumsen & Christoffersen, 1992), and passive and active inward fluxes of Cl-have been localized to MR cells, with the active component energized by the apical proton pump (Vofute & Meyer, 1978;Larsen, 1991;. Finally, an apical amiloride-blockable Na+ influx mechanism and basolateral Na+-K+ pumps are present in MR cells, indicating that they also mediate active uptake of Na+ (Larsen, Ussing & Spring, 1987;Harvey, 1992;Rick, 1992).…”
mentioning
confidence: 99%
“…We have previously suggested that the IMRCs in the ammocoete gills belong to the subtype A or C [11], which cannot be distinguished in the presence of H-ATPase and rod-shaped particles in their apical membrane alone. The view that many of the IMRCs in the ammocoete gill epithelium belong to the subtype C is supported by the observation of Reis-Santos and co-workers [7] that many of these cells show a strong cytoplasmic immunoreactivity for H + -ATPase, which is typical for this subtype [13,34]. Thus, an active H + secretion through the subtype A and C cells would not only provide the driving force for the uptake of Na + but also favour the uptake of Cl − through subtype C cells as the actively secreted H + can bind to the HCO 3 − as it leaves the cell through the apical membrane and thereby establish an HCO 3 − gradient across this membrane which would drive the uptake of Cl − [13].…”
Section: Resultsmentioning
confidence: 55%
“…On the basis of their ultrastructure and the presence of H + -ATPase and carbonic anhydrase, the lamprey IMRC is a type of epithelial cell that also occurs, for example, in the amphibian epidermis, the toad and turtle urinary bladders and renal collecting duct [7,11,13,30,31]. This cell type comprises three subtypes: one (A) containing the H + -ATPase in its apical membrane and an HCO 3 − /Cl − exchanger in its basolateral membrane, another (B) exhibiting the opposite locations of the H + pump and the anion exchanger and a third (C) in which the H + pump and the anion exchanger are both located in the apical membrane [32][33][34]. Whereas the subtypes A and B are involved in acid-base regulation, secreting H + or HCO 3 − , respectively, the subtype C has been held responsible for the uptake of Cl − [32][33][34].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation